The Promising Prospect of Banana Production and Marketing in Indonesia - Bambang Yudi Ariadi; Rahayu Relawati; Lorenta In Haryanto; Mohd Fauzi Kamarudin; Yohana Agustina (SOCA: Jurnal Sosial Ekonomi Pertanian, 2024)
Despite its well-run production and marketing in Indonesia, the development strategies of banana produce are in need of comprehensive scientific study. This present study aims to analyze the production and marketing prospects of Indonesian bananas. We employed the available data from the Central Bureau of Statistics (Badan Pusat Statistik) from 2017-2021. The obtained data for production prospects was analyzed through a descriptive analysis by compiling the numbers of production, productive crops, and productivity of bananas. Meanwhile, the marketing prospects were analyzed based on data on consumption, export volume and value, import volume and value, and exports and imports of banana flour. The results showed that the prospects for banana production in Indonesia are promising; however, the production development is in need of support from more planting areas to boost productivity. Marketing expansion into the importing-countries, such as Europe, the US, China, Russia, and Japan is facilitated through the export of fresh bananas. Our findings suggest that the marketing prospects can be increased through the support from banana processing industry. Furthermore, the opportunity for market expansion of processed banana products remains viable in both domestic and international markets, particularly when considering banana flour as a potential product.